Analisis Truck Round Time di Lapangan Petikemas Ekspor dalam Kegiatan Receiving di Terminal Petikemas Koja - Salman Al Farisi; Vivian Karim Ladesi; Winoto Hadi; Siti Sahara; Kencana Verawati (Journal of Management and Bussines (JOMB), 2024)
This research aims to identify the causes of problems or obstacles related to receiving activities, starting from trucks entering the gate-in to leaving the gate-out at the Koja Container Terminal, and providing an understanding of the impacts resulting from the identified problems or obstacles. The research method used is descriptive qualitative, which describes and explains the conditions, phenomena or research variables studied. Truck Round Time analysis at the export container terminal shows that there are several obstacles in the process of receiving containers at the stacking yard. The time of receiving activities can be seen from the length of Truck Round Time, where only 33% of that time reaches the ideal standard, while 67% is still below the ideal standard. The length of time for receiving activities that do not reach ideal standards has negative impacts, such as the potential for congestion inside or outside the terminal, which can harm the good name of the Koja Container Terminal, reduce customer loyalty and satisfaction with the terminal, and hamper other operational processes within. Keywords: Receiving, Container Terminal, Truck Round Time